Experimental Determination of the Orientation of Tilted Magnetic Anisotropy by Using Angle-Resolved Hall Effect Signals - Piskin, H.; Demirci, E.; Ozturk, M.; Akdogan, N. (Springer, 2021)
The orientation of the tilted magnetic anisotropy has crucial importance in many spintronic devices. However, it is very challenging to determine it especially in very small structures produced by lithography. Here, we propose a new experimental method to directly and accurately measure both the polar and azimuthal angles of a tilted magnetic anisotropy by using anomalous and planar Hall effects together. We named this as the angle-resolved Hall effect signals' (ARHES) method. By using the proposed method, an obliquely deposited multilayer structure of Pt(4)/[Co(0.5)/Pt(0.5)] x 5/IrMn(8)/Pt(3) (nm) has been investigated. The out-of-plane (24.4 degrees) and in-plane (219 degrees) angles of the tilted magnetic anisotropy in the sample have been successfully determined from the experiments. The accuracy of the ARHES method has also been confirmed by theoretical calculations that give the same polar and azimuthal angles of the magnetic anisotropy.
Keywords: Tilted magnetic anisotropy; Orientation of magnetization; Anomalous Hall effect; Planar Hall effect; Rotatable magnetic anisotropy